Prevalence of Peri-Implantitis in Implants with Turned and Rough Surfaces: a Systematic Review - Nikola Saulacic; Benoit Schaller (Stilus Optimus, 2019)
Objectives: Moderately-rough implant surface may improve implant therapy in terms of bone integration, but the increased surface roughness might affect the initiation and development of peri-implantitis. The aim of the present review was to compare the prevalence of peri-implantitis in implants with rough and turned (machined) implant surfaces. Material and Methods: An electronic literature search was conducted of the MEDLINE and EMBASE databases for articles published between 1 January 1990 and 1 March 2018. Clinical human studies in the English language that had reported on prevalence of peri-implantitis in tuned and rough surface implants searched. The initial search resulted in 690 articles. Results: Eight articles with 2992 implants were included in the systematic review. The incidence of peri-implantitis for two implant surfaces varied between studies. A meta-analysis was not feasible due to the heterogeneity among studies. Implant with rough surfaces were more favourable for plaque accumulation during short-term follow-up. On a long-term, turned implants surfaces were associated with more plaque and higher peri-implant bone loss. Peri-implant clinical parameters and survival rate for two implant surfaces was similar. Conclusions: Within the limitations of the present study, rough implant surface does not seem to increase the incidence of peri-implantitis in comparison to turned implants surface.